Performance Analysis of Indirect Rotor Field Orientation Five Phase Induction Motor Using Eight Switch Inverter - Mahmoud Mohamed Elkholy; Zakaria M.S. Elbarbary (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper proposes new topology of five-phase inverter with reduced number of switches fed indirect rotor field oriented five phase induction motor. It employs only eight IGBT switches preformed five phase inverter. The reduction of the number of power switches from ten to eight improves the cost-effectiveness, volume-compactness and reliability of five-phase induction motor drive system. Simulation model of the proposed drive system is developed using the Matlab/Simulink package and analyzed to verify the effectiveness at different operating conditions of this approach. The comparison between the performance of the five phase motor under classical ten switch inverter and new topology at the same operation conditions has been illustrated. The proposed system gives similar operations as classical ten switch inverter for a certain range of motor speed and load torque. The DC voltage of proposed inverter must be compensated to higher value to achieve same performance of classical ten switch inverter in all range of motor speed and load torque.